INT-013 Developing a manipulation guideline for solid oral dosage forms to ease swallowing. (2nd March 2018) - Bjerknes, KCF; Buan, L; Rise, T; Vukovic, M; Pedersen, E; Rognan, SE; Fjørkenstad, A; Lundstrøm, C; Norheim, AM; Brummenæs, HE; Davidsson, M; Bruun, LI
Abstract : Background: Patients with swallowing challenges may require manipulated solid oral dosage forms of drugs in order to achieve proper treatment. Manipulation of drugs, by means of crushing, dividing or mixing tablets with food or water could be the solutions to this. Deviations from standard administration may alter the effect of drugs or cause other negative consequences, such as irritated mucus membranes. Healthcare providers need easy access to information on this matter. Purpose: Examine whether various drugs in solid oral dosage forms may be manipulated, and develop a guideline to make this information readily available to healthcare providers at Oslo University Hospital. Materials and Methods: Drugs in solid oral dosage forms were chosen based on relevance to Oslo University Hospital. Standardised log sheets with selected sources were developed and applied to each drug by a pharmacist. Based on the information gathered the pharmacist concluded with a recommendation concerning manipulation of each drug. A second pharmacist controlled the information and conclusions. The conclusions were harmonised in regards to formulation and the Anatomical Theraputic Chemical Classification (ATC) System. According to the guideline, manipulation should occur immediately before administration and therefore degradation due to light and/or humidity was not taken into account. Results: Eight hundred and fifty-five drugs in solid oral dosage forms were included in a guideline with recommendations on how to manipulate them. The list is available through the quality management system of Oslo University Hospital. Hospital staff can receive training upon request from the pharmacists concerning use of the guideline. Conclusions: A guideline comprising information on how to manipulate 855 drugs in solid oral dosage forms has been developed and made available to healthcare providers at Oslo University Hospital.